Integrasi Ilmu dan Agama dalam Kajian Islam Kontemporer: Kajian Kepustakaan tentang Relevansi Pendekatan Multidisipliner - David Ricardo; Ahmad Arifi (Advances In Education Journal, 2025)
Contemporary Islamic studies face complex social, cultural, and intellectual challenges that require more comprehensive and adaptive scholarly approaches. This study aims to analyze the concept of integrating science and religion and to examine the relevance of a multidisciplinary approach in strengthening the paradigm of Islamic scholarship. Employing a qualitative method with a library research design, the study is analyzed through a phenomenological perspective to explore the intellectual experiences of Muslim thinkers in understanding the relationship between revelation, reason, and empirical reality. The findings indicate that the integration of science and religion constitutes an epistemological characteristic deeply embedded in the Islamic intellectual tradition, while the multidisciplinary approach provides a richer analytical framework for interpreting contemporary religious phenomena. This approach expands the scope of inquiry through the engagement of social sciences, humanities, and modern sciences, thereby enabling a more contextual and relevant understanding of religion. The implications of this study highlight the importance of strengthening an interconnective paradigm in curriculum development, research methodology, and Islamic studies. Overall, the study concludes that a multidisciplinary approach represents an epistemological necessity for the development of comprehensive and responsive contemporary Islamic studies.